Performance investigation of grid-connected residential PV-battery system focusing on enhancing self-consumption and peak shaving in Kyushu, Japan. (November 2018) - Li, Yanxue; Gao, Weijun; Ruan, Yingjun
Abstract: With increasing PV penetration level, performances of the distributed grid-connected PV system and aggregated effects on public grid need to be identified and analyzed. This paper simulated the techno-economic performances of the grid-connected residential PV-battery system based on simulated PV generations, history household load, technical and economical parameters under the electricity market in Kyushu, Japan. Results indicate that residential PV self-consumption ratios vary significantly between months, it can increase by adding relative battery size, the increasing rate shows obvious variations between months and its value highly depends on features of the customer load and PV generation profiles. Optimal management strategies for private home storage dispatch show a potential in grid peak load shaving. Assumed accumulative generation of home PV-battery system totally shares 2.0% of grid load, analysis indicates that proposed grid-supporting PV-battery systems can participate in 1.1% reduction of peak grid load. The economic feasibility and uptake of battery system highly depend on direct subsidies due to high capacity cost, payback period of PV-battery system is around 18 years without any incentive policies. Increasing electricity pricing, decreasing PV feed-in tariff and falling cost in battery can provide the home PV-battery system more attractiveness. Highlights: Self-consumption rate and self-sufficiency degree show great variations between months. Analysis of PV self-consumption ratio by adding different relative battery sizes. Aggregated optimized residential PV-battery system can release the public grid pressure. Incentive subsidy to battery unit is essential to shorten the payback period of PV-battery system.